Electrical impedance estimation for pork tissues during chilled storage. (March 2020) - Leng, Yue; Sun, Yonghai; Wang, Xiaodan; Hou, Jumin; Zhao, Xutong; Zhang, Yuxia
Abstract: The impedance and physicochemistry of pork loins at five chilled storage periods (0, 1, 3, 7, 15 days) were characterized in order to explore the effects of chilling on the cell physiological status of pork tissues. The impedance spectra were analyzed by an equivalent circuit model with needle and bar electrodes. Meat traits including cooking loss, color, pH, texture properties and electrical conductivity were measured. The conductivity and pH of pork increased, and the color and texture parameters all significantly differed. The measured impedance of pork tissues can be described well by a modified Hayden model. The impedance characteristics of samples revealed that the structures and integrity of cell membranes in pork tissues were damaged with the prolonged storage time. The findings prove the potential of electrical impedance spectroscopy in evaluating the physiological status of pork tissues during chilled storage.